Successful sequential tyrosine kinase inhibitors to overcome a rare compound of EGFR exon 18–18 and EGFR amplification: A case report - Wang, Pascal; Fabre, Emmanuelle; Martin, Antoine; Chouahnia, Kader; Benabadji, Ambre; Matton, Lise; Duchemann, Boris (Frontiers in Oncology, 2022)
Background: New mutational detection techniques like next-generation sequencing have resulted in an increased number of cases with uncommon mutation and compound mutations (3– 14% of all EGFR mutations). In rare exon 18 mutations (3-6%), G719X and E709X represent the majority but CMut associating these exon 18 points mutations are even rarer, making the understanding of epidermal growth factor receptor tyrosine kinase inhibitors impact still limited. Three generations of EGFR TKIs are available to target EGFR mutations but according to the types of mutations, the sensitivity to TKI is different. Afatinib, osimertinib and neratinib have showed some effectiveness in single exon 18, but none report have yet precisely described their efficiency and acquired mechanism of resistance in a CMut of exon 18-18 (G719A and E709A). Case presentation: We report a case of a 26-year-old female with bilateral advanced adenocarcinoma of the lung harboring a compound mutation associating G719A and E709A in exon 18 who developed an EGFR amplification as resistance’s mechanism to osimertinib. She presented a significant clinical and morphologic response under sequential TKIs treatment (afatinib, osimertinib, and then neratinib). Conclusion: A NSCLC with rare compound mutation exon 18-exon 18 (G719A and E709A) and EGFR amplification can be overcome with adapted sequential second and third generation TKIs. This report has potential implications in guiding decisions for the treatment of these rare EGFR mutations.